백운석 첨가가 응집에 의한 하수 처리수의 인 제거에 미치는 영향 - 이병하; 박준홍; 차호영; 맹승규; 송경근 (대한상하수도학회, 2012)
Wastewater treatment plants need to reduce phosphorus in order to meet increasingly stringent regulations on phosphorus. This study evaluated the feasibility of dolomite as a coagulation aid to enhance phosphorus removal from secondary treated wastewater by chemical coagulation. Standard jar tests were conducted to evaluate the effect of dolomite addition on a coagulation process for phosphorus removal and to determine the optimum doses of coagulants and dolomite. Coagulants used with dolomite yielded a significant improvement in phosphorus removal and reduced total phosphorus concentrations below 0.02 mg/L in wastewater effluent. Dolomite has played an important role in enhancing phosphate adsorption and increasing pH, as a coagulation aid. The maximum removal efficiency of phosphorus in this study was yielded at 25 mg/l of dolomite and 20 mg Al/L of PAC dose. However, considering economic aspects, the optimum doses of dolomite and PAC were 10 mg/L and 15mg Al/L, respectively. Consequently, dolomite, a coagulation aid, can be used in coagulation processes to enhance the removal of phosphorus.